2022
DOI: 10.1021/acs.biomac.2c00626
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Modified Polypyrrole-Coated PLCL and PLGA Nerve Guide Conduits Fabricated by 3D Printing and Electrospinning

Abstract: The efficiency of nerve guide conduits (NGCs) in repairing peripheral nerve injury is not high enough yet to be a substitute for autografts and is still insufficient for clinical use. To improve this efficiency, 3D electrospun scaffolds (3D/E) of poly­(l-lactide-co-ε-caprolactone) (PLCL) and poly­(l-lactide-co-glycolide) (PLGA) were designed and fabricated by the combination of 3D printing and electrospinning techniques, resulting in an ideal porous architecture for NGCs. Polypyrrole (PPy) was deposited on PLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 79 publications
1
20
0
Order By: Relevance
“…This decrease is attributed to the brittle nature of the aromatic rings present in polypyrrole and polyaniline. 54,55 Contrarily, the composite films presented an increase in their modulus of elasticity as compared to the pure PLA film. This behavior became more evident in the film coated with polyaniline (PLA−PANi-3h), since it presented Young's modulus of 1609.63 MPa.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This decrease is attributed to the brittle nature of the aromatic rings present in polypyrrole and polyaniline. 54,55 Contrarily, the composite films presented an increase in their modulus of elasticity as compared to the pure PLA film. This behavior became more evident in the film coated with polyaniline (PLA−PANi-3h), since it presented Young's modulus of 1609.63 MPa.…”
Section: Resultsmentioning
confidence: 94%
“…First, a slight decrease in tensile strength was observed for both composite materials, presenting values of 43.20 and 43.90 MPa for the PLA–PPy-1h and PLA–PANi-3h films, respectively. This decrease is attributed to the brittle nature of the aromatic rings present in polypyrrole and polyaniline. , Contrarily, the composite films presented an increase in their modulus of elasticity as compared to the pure PLA film. This behavior became more evident in the film coated with polyaniline (PLA–PANi-3h), since it presented Young’s modulus of 1609.63 MPa.…”
Section: Resultsmentioning
confidence: 96%
“…One type is close to the physiological temperature. Guo et al found that the SMP polymer made of PLCL and poly(l-lactide- co -glycolide) (PLGA) has a shape recovery rate of up to 100% when the temperature is close to the human body temperature, and the SMP material shows high elasticity at 37 °C [ 33 ]. The second type is higher than the physiological temperature.…”
Section: Smps and Their Properties In Response To Different Stimulationsmentioning
confidence: 99%
“…12−14 3D printing is a tailorable and user-friendly technology for producing 3D architectures, but the printing resolution is significantly limited to the microscale. 12,15 Freezedrying is another simple and effective method for the fabrication of 3D architectures, and the resulting materials generally present nonfibrous structures. 13,16 Self-assembly can be used to fabricate amyloid-like fibrils.…”
mentioning
confidence: 99%
“…Different methods such as 3D printing, freeze-drying, and self-assembly have been developed to produce biomaterials. 3D printing is a tailorable and user-friendly technology for producing 3D architectures, but the printing resolution is significantly limited to the microscale. , Freeze-drying is another simple and effective method for the fabrication of 3D architectures, and the resulting materials generally present nonfibrous structures. , Self-assembly can be used to fabricate amyloid-like fibrils. , However, it is very difficult to obtain the desired dimensions and structures of nanofibers and nanofibrous materials with natural polymers by this method because the fabrication process is influenced by multiple factors such as molecular sequence and size, pH, temperature, and solvents. , Currently, ECM-mimicking biomaterials based on nanofibers (diameter of <1 μm) and microfibers (diameter of ≥1 μm) have been developed for biomedical applications. , However, the fabrication of nanofibers relies mostly on electrospinning technology. A 3D nano/microfibrous composite matrix can be fabricated by combining electrospinning with a microfiber-producing technique such as melt deposition or 3D printing. , Unfortunately, these approaches present several challenges. First, the electrospinning of nanofibers requires a high concentration and suitable viscosity of the polymer (e.g., protein or polysaccharide) solution. For example, to electrospin silk fibroin nanofibers, the concentration of silk fibroin in an aqueous solution has to be around 20% (w/v) or even higher. , Although some solvents such as hexafluoroisopropanol or trifluoroacetic acid can be used instead to decrease the concentration of natural polymers in the electrospinning processing, they are very toxic and environmentally unfriendly. Second, many pure natural proteins and polysaccharides such as alginate could not be electrospun into nanofibers due to the high viscosity and gelation-sensitive characteristics of their solutions even at a low concentration. , Third, the pores of electrospun nanofibrous networks are very small due to the layer-by-layer deposition of electrospun nanofibers, which significantly limits the infiltration of cells .…”
mentioning
confidence: 99%